1986
DOI: 10.1161/01.hyp.8.11.990
|View full text |Cite
|
Sign up to set email alerts
|

Potassium depletion ameliorates hypertension in spontaneously hypertensive rats.

Abstract: SUMMARY The hemodynamic effect of moderate K+ depletion in hypertension is unknown. Since severe K+ depletion reduces systemic vascular resistance in normotensive rats, we determined the effect of K+ depletion on the natural history of hypertension in spontaneously hypertensive rats (SHR). Wistar-Kyoto rats (WKY) and SHR were fed a K + -replete, a moderately K + -depleted, or a severely K + -depleted diet. After 6 weeks, systemic vascular resistance was reduced by 25% in WKY on the severely K + -depleted diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 27 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Numerous human epidemiological studies have indicated an inverse correlation between K ϩ intake and blood pressure (5, 15, 19, 28a, 29, 51). Despite this strong association, studies in animal models using standardized diets have had conflicting results (1,3,15,20,24,33,36,42,60,63,68). To address this dilemma, researchers have turned to animal models and standardized diets to study the effect of dietary K ϩ on blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous human epidemiological studies have indicated an inverse correlation between K ϩ intake and blood pressure (5, 15, 19, 28a, 29, 51). Despite this strong association, studies in animal models using standardized diets have had conflicting results (1,3,15,20,24,33,36,42,60,63,68). To address this dilemma, researchers have turned to animal models and standardized diets to study the effect of dietary K ϩ on blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, the induction of hypotension by a complete K + restriction has been described in many studies using different animal species [18,21,28], however, in humans for reasons discussed below reduction of K + intake is generally related to hypertension. In the present study, we tried to understand the mechanisms linking K + balance and the control of the BP.…”
Section: Discussionmentioning
confidence: 99%
“…Studies focusing on the impact of a low daily intake of K + in humans have demonstrated a positive correlation with the probability for developing hypertension by mechanisms that remain partly unsettled [7,14,19]. Conversely, analysis of K + -depleted animal models (normal or hypertensive) suggests that a low K + intake induces a decrease in blood pressure (BP) [18,21,28]. This discrepancy is probably not related to species differences in the blood pressure response to dietary K + restriction but is rather due to the degree of K + restriction, which is moderate in human studies and almost complete in animal studies but also to the large amount of Na + normally ingested by the general population compared to the experimental models.…”
Section: Introductionmentioning
confidence: 99%
“…However, this BP response of adult involves a direct stimulation of renin-secreting cells in humans and rodents to changes in potassium balance the juxtaglomerular apparatus and is mediated by the varies greatly according to the clinical or experimental renal vascular receptor [34]. In our study, ECF volume conditions [6][7][8][9][10][11][12]. Consequently, there is controversy in contraction may also be contributing to the increased relation to the specific effects of potassium depletion PRA.…”
Section: Discussionmentioning
confidence: 99%